Masked Potentials, Hidden Struggles? A Scoping Review of Twice-Exceptional Individuals’ Transition to Employment - Ruben Heuving; John Exalto; Alexander Minnaert (Social Sciences)
This study examined the transition of twice-exceptional (2E) individuals from education to employment. Despite a growing focus on inclusive practices, the area of (special) education-to-work transition is still far under-researched, especially on 2E individuals. To identify challenges and success factors in this transition, a scoping review method was used. Our review revealed a paucity of targeted studies on the transition of 2E individuals to work. Four relevant studies, focusing primarily on higher education, emphasized strengths-based approaches and multi-stakeholder support to facilitate transitions. The findings underscore the need for tailored interventions and supportive environments, addressing both individual strengths and (environmental) barriers. Further research is essential in view of effective interventions to bridge the gap between education and employment for 2E individuals.